PUBLIC-PRIVATE PARTNERSHIPS IN ENGINEERING TALENT DEVELOPMENT IN SOUTH KOREA’S EDUCATION SYSTEM (Scientific journal of the Fergana State University, 2025)
South Korea’s rapid industrial and technological progress has been supported by an education system that is closely aligned with industry needs. Public-private partnerships (PPPs) play a key role in this ecosystem, enabling the development of engineering talent through collaboration between government, academia, and industry. This article examines the South Korean PPP model in engineering education, highlighting key strategies such as co-development of curricula, industry-sponsored internships, collaborative research initiatives, and government incentives. The article also examines challenges and potential solutions in implementing effective PPPs, and provides insights for countries seeking to replicate South Korea’s success in aligning educational outcomes with market demands. Ultimately, South Korea’s PPP-based approach serves as a global benchmark for promoting innovation, workforce readiness, and sustainable economic growth.